The Origination of Growth Hormone/Insulin-Like Growth Factor System: A Story From Ancient Basal Chordate Amphioxus - Li, Mengyang (Frontiers in Endocrinology, 2022)
The growth hormone/insulin-like growth factor (GH/IGF) system, also called the pituitary-liver axis, plays somatotrophic roles. Although the GH/IGF system has always been regarded as a vertebrate-specific endocrine system, its actual origin has remained unknown for a long time. The basal chordate, amphioxus, occupies an evolutionary position between vertebrates and invertebrates. Impressively, most of the members of the GH/IGF system are present in the amphioxus. The GH-like molecule in the amphioxus is mainly expressed in Hatschek’s pit. It functions similar to vertebrate GH and has a GH receptor-like binding partner. The amphioxus IGF-like peptide shows mitogenic activity and an expression pattern resembling that of vertebrate IGF-I. The receptor of IGF-like peptide and IGF binding protein (IGFBP) have also been demonstrated to exist in the amphioxus. These results reveal the origin of the gene families in the GH/IGF system, providing strong evidence that this system emerged in the amphioxus.